Low warpage polyamide material for large size thin wall cover and preparation method thereof

CN122958849APending Publication Date: 2026-10-23SHANGHAI PRET COMPOSITES +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611260657.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,常规玻璃纤维在注塑流动方向上产生明显的取向,导致材料在流动方向(MD)和垂直方向(TD)上的热收缩率存在显著差异

Benefits of technology

[0020]本发明通过“PA6/共聚尼龙复配基体+扁平玻纤+改性金云母+负热膨胀助剂”的四元协同设计,实现了低翘曲、高尺寸稳定性和优良加工流动性的统一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958849A_ABST
    Figure CN122958849A_ABST
Patent Text Reader

Abstract

The application discloses a low-warp polyamide material for large-size thin-wall cover and a preparation method thereof. The material is prepared from the following raw materials in parts by weight: polyamide resin 60-70 parts, flat glass fiber 5-10 parts, modified phlogopite 15-25 parts, negative thermal expansion aid 1-5 parts, antioxidant 0.2-0.5 parts, and other aids 0.2-1 part. The negative thermal expansion aid can reversibly shrink the lattice within the range of 30-600 DEG C, and the negative expansion effect can offset the normal thermal expansion of the polyamide matrix and the filler, so that the thermal cycle stress is eliminated. The polyamide material has excellent anti-warping performance, and the processing fluidity of the material is improved, and the polyamide material can be applied to large-size thin-wall engine covers and other automobile parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials technology, specifically relating to a low-warpage polyamide material suitable for automobile engine covers and its preparation method. Background Technology

[0002] Polyamides are widely used in automotive engine peripheral components due to their excellent mechanical properties, heat resistance, chemical corrosion resistance, and good processing performance. However, although polyamide resins have excellent processing fluidity, their high crystallinity and large molding shrinkage, especially glass fiber reinforced polyamide materials, can significantly improve the mechanical strength and heat distortion temperature of the material, but are prone to serious surface fiber floating and warping deformation problems when manufacturing large-sized thin-walled products (such as engine hoods).

[0003] In recent years, with the trend of lightweighting in automobiles, engine hoods have evolved towards larger sizes and thinner walls, placing more stringent demands on the low warpage and dimensional stability of materials. To reduce anisotropy, mineral fillers (such as talc) are often used in industry to partially replace glass fibers. For example, Chinese patent application CN101875780A discloses a polyamide composite material, which includes the following components by weight: 26-71 parts of nylon 66, 20-40 parts of conventional glass fiber, 10-25 parts of kaolin, 0.1-1 parts of antioxidant, 0.2-2 parts of heat stabilizer, 0.1-1 parts of lubricant, 0.1-1 parts of dispersant, and 0.5-2 parts of colorant; Chinese patent application CN108102363A discloses a high-temperature resistant, low-warpage nylon composite material for automobile engine hoods, which includes the following components by weight: 40-80 parts of nylon 66, 10-30 parts of glass fiber, 10-30 parts of mineral filler, 5-9 parts of TPO, 0.5-2 parts of lubricant, 0.1-0.8 parts of antioxidant, 0.2-1.7 parts of heat stabilizer, and 0.7-2.5 parts of colorant. However, conventional glass fibers exhibit a pronounced orientation in the injection molding flow direction, resulting in significant differences in thermal shrinkage rates between the flow direction (MD) and the vertical direction (TD). For large-sized, thin-walled covers, this anisotropic shrinkage generates substantial internal stress during cooling, ultimately leading to warping and deformation of the product. Furthermore, conventional mineral fillers such as talc have a positive coefficient of thermal expansion, expanding with increasing temperature in high-temperature environments (e.g., 80-150°C in engine compartments), causing a decrease in material dimensional stability. Consequently, covers may deform or fail to seal during long-term high-temperature service.

[0004] Therefore, developing a polyamide material that combines low warpage, good appearance, and excellent processing flowability, suitable for large-size thin-walled engine covers, has become a pressing technical challenge in this field. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects and shortcomings of the prior art and provide a polyamide material and its preparation method that has low warpage, good appearance and excellent processing flowability, suitable for large-size thin-walled engine covers.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a low-warpage nylon material for covers, which is composed of the following components by weight: 60-70 parts of polyamide resin, 5-10 parts of flat glass fiber, 15-25 parts of modified phlogopite, 1-5 parts of negative thermal expansion agent, 0.2-0.5 parts of antioxidant, and 0.2-1 parts of other additives.

[0008] Preferably, the polyamide resin is a mixture of low-viscosity PA6 resin and copolymer nylon resin, and the addition ratio (by weight) of PA6 resin and copolymer nylon is 1:3 to 2:1.

[0009] Furthermore, the low-viscosity PA6 has a relative viscosity of 2.0 (96% sulfuric acid solution, 1 g / dL, measured at 25°C), a melt flow rate (250°C / 0.325 kg) of 31 g / 10 min, and a melting point of 220°C.

[0010] Furthermore, the copolymer nylon is a copolymer of PA6 and PA66, with a relative viscosity of 2.5 (96% sulfuric acid solution, 1 g / dL, measured at 25°C), a melt flow rate (250°C / 0.325 kg) of 4.6 g / 10 min, and a melting point of 202°C.

[0011] Preferably, the flat glass fiber has a flat cross-section with an aspect ratio (width / thickness) of 2:1 to 6:1.

[0012] Preferably, the negative thermal expansion additive is a zirconium phosphate-based negative thermal expansion material, which is cubic in appearance and has a density of 0.2 g / cm³. 3 It has a reversible negative coefficient of thermal expansion (CTE) of -3.5 × 10⁻⁶ within the temperature range of 30–600℃. -6 / K).

[0013] Preferably, the modified phlogopite is phlogopite powder surface-treated with a silane coupling agent. The phlogopite has a D50 of 35 μm, a pH of 9, a bulk density of 0.25 kg / L, and contains 41.5% SiO2, 24.0% MgO, 10.5% K2O, and 10.0% Al2O3.

[0014] Furthermore, the modified phlogopite is prepared through the following steps:

[0015] (1) Acid washing and activation of phlogopite: Phlogopite powder was immersed in a 0.1 mol / L dilute hydrochloric acid solution with a solid-liquid ratio of 1:5 (mass-volume ratio) and stirred at 40°C for 30 minutes. This process dissolves some interlayer potassium ions, generates more active Si-OH groups on the surface, and cleans surface impurities. The acid-treated slurry was then repeatedly filtered and washed with deionized water until the pH of the filtrate was 6.5–7.0. Finally, the filter cake was dried in a forced-air dryer at 120°C for 4 hours to initially remove surface free water and obtain activated phlogopite powder.

[0016] (2) Preparation of KH-550 hydrolysate: In an independent container, prepare the hydrolysate according to the following ratio (based on the treatment of 1000g of phlogopite): mix 1000g of deionized water and 3000g of anhydrous ethanol evenly, and slowly add 15g of KH-550 silane coupling agent while stirring. Adjust the pH to 8.0-8.5 with glacial acetic acid, and pre-hydrolyze at 25℃ for 30 minutes to obtain a clear and transparent slightly alkaline hydrolysate.

[0017] (3) Modification process: First, add 1000g of activated phlogopite to a high-speed mixer (with heating function) and preheat to 90℃ under low-speed stirring (500rpm). Then, the prepared KH-550 hydrolysate is slowly and evenly sprayed into the phlogopite powder through an atomizing nozzle under high-speed stirring (1500rpm) for 15-20 minutes. After spraying, the mixer temperature is raised to 110℃ and the reaction is continued for 45-60 minutes while maintaining high-speed stirring. During this process, the silanol groups of silane condense with the hydroxyl groups on the surface of phlogopite to form a stable Si-O-Si (phlogopite) chemical bond, while excess water and ethanol are evaporated. Finally, the treated material is taken out and placed in a vacuum oven and vacuum-cured at 120℃ for 2 hours to completely solidify and crosslink the coupling layer, resulting in modified phlogopite with a hydrophobic surface and good affinity with the nylon matrix.

[0018] Secondly, the present invention provides a method for preparing the above-mentioned low-warpage polyamide material for large-size thin-walled covers, comprising the following steps: mixing weighed polyamide resin, antioxidant and other additives uniformly in a high-speed mixer to obtain mixture A, which is added from the main feed of a twin-screw extruder; mixing modified phlogopite and negative thermal expansion additive uniformly in a high-speed mixer to obtain mixture B; adding flat glass fibers and mixture B from two sides respectively; and obtaining a polyamide composition with good appearance and low warpage after melt extrusion, granulation and drying processes.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] This invention achieves a balance of low warpage, high dimensional stability, and excellent processing flowability through a quaternary synergistic design of "PA6 / copolymer nylon composite matrix + flat glass fiber + modified phlogopite + negative thermal expansion additive".

[0021] (1) Low shrinkage and self-toughening properties of PA6 / copolymer nylon composite matrix

[0022] The introduction of copolynylon disrupts the regularity of the PA6 molecular chain, significantly reducing the crystallinity of the matrix and drastically decreasing its molding shrinkage, thus fundamentally reducing the warpage driving force. Simultaneously, copolynylon exhibits good compatibility with PA6, enabling the formation of micro-phase separation or molecular-level mixed structures, endowing the material with excellent low-temperature toughness.

[0023] (2) Flat glass fibers reduce anisotropic shrinkage

[0024] When flat glass fibers flow during injection molding, their width direction is oriented along the flow direction, while their thickness direction tends to be randomly distributed, which effectively reduces the difference in shrinkage rate in the MD / TD direction and reduces internal stress from the source.

[0025] (3) Modified phlogopite provides two-dimensional dimensional stability

[0026] Surface treatment with a silane coupling agent significantly improves the compatibility between lamellar phlogopite and polyamide matrix resin. The modified phlogopite sheets with a large aspect ratio are oriented along the planar direction during injection molding, providing strong physical constraint on internal thermal expansion while allowing free shrinkage in the thickness direction, perfectly matching the stress distribution of thin-walled parts. Compared with conventional fillers such as granular talc, the constraint efficiency of lamellar phlogopite is significantly improved.

[0027] (4) Negative thermal expansion additives precisely compensate for high-temperature thermal expansion.

[0028] Zirconium phosphate-based negative thermal expansion additives undergo reversible lattice contraction in the range of 30–600℃. Their negative expansion effect can counteract the normal thermal expansion of the polyamide matrix and fillers, reducing the overall CTE of the material to a level close to that of metals and eliminating thermal cycling stress.

[0029] (5) Synergistic coordination effect of modified phlogopite and negative thermal expansion additive

[0030] Under specific ratios, modified phlogopite and negative thermal expansion additives form a "layer-particle" composite functional body. This structure enables physical constraints and negative expansion chemical compensation to work synergistically at the micro-nano scale, achieving a 1+1>2 effect of reducing expansion and resisting warping. Attached Figure Description

[0031] Figure 1 The image shown is a scanning electron microscope image of the negative thermal expansion additive in the example. Detailed Implementation

[0032] The present invention will be further described in detail below through examples and comparative examples.

[0033] The raw material information is as follows:

[0034] PA6 resin: Baling Petrochemical YH800, relative viscosity 2.0 (96% sulfuric acid solution, 1g / dL, measured at 25℃), melt flow rate (250℃ / 0.325kg) 31g / 10min, melting point 220℃;

[0035] Copolymer Nylon: HY2000A, Haiyang, Jiangsu Province, with a relative viscosity of 2.5 (96% sulfuric acid solution, 1 g / dL, measured at 25℃), a melt flow rate (250℃ / 0.325 kg) of 4.6 g / 10 min, and a melting point of 202℃;

[0036] Flat fiberglass: 301HP-3-M4, Chongqing International;

[0037] Round fiberglass: 301HP-3-H, Chongqing International;

[0038] Talc powder: SD-9042 (3000 mesh), Liaoning Xinda Talc Group Co., Ltd.;

[0039] Negative thermal expansion additive: ULTEA® WJ1, Toa Synthetic Co., Ltd., in cube form (e.g., Figure 1 As shown), the density is 0.2 g / cm³. 3 It exhibits a reversible negative coefficient of thermal expansion (CTE) within the temperature range of 30–600℃, with a CTE of -3.5 × 10⁻⁶. -6 / K;

[0040] Antioxidants: including antioxidant 1098 and copper salt antioxidant (H324, Brügmann), both of which are commercially available;

[0041] Other additives: including lubricant (BRO-R05, HeCai Chemical Technology) and black masterbatch, all of which are commercially available;

[0042] Phlogopite: PW80, Mouheng Materials Technology (Shanghai) Co., Ltd., D50 35μm, pH 9, bulk density 0.25kg / L, SiO2 content 41.5%, MgO content 24.0%, K2O content 10.5%, Al2O3 content 10.0%;

[0043] Modified phlogopite, prepared in-house, is prepared as follows:

[0044] (1) Acid washing and activation of phlogopite: Phlogopite powder was soaked in a 0.1 mol / L dilute hydrochloric acid solution with a solid-liquid ratio of 1:5 (mass-volume ratio) and stirred at 40°C for 30 minutes; then the acid-treated slurry was repeatedly filtered and washed with deionized water until the pH of the filtrate was 6.5-7.0; finally, the filter cake was dried at 120°C for 4 hours to initially remove the surface free water and obtain activated phlogopite powder.

[0045] (2) Preparation of KH-550 hydrolysate: In an independent container, prepare the hydrolysate according to the following ratio (based on the treatment of 1000g of phlogopite): mix 1000g of deionized water and 3000g of anhydrous ethanol evenly, and slowly add 15g of KH-550 silane coupling agent while stirring. Adjust the pH to 8.0-8.5 with glacial acetic acid, and pre-hydrolyze at 25°C for 30 minutes to obtain a clear and transparent slightly alkaline hydrolysate.

[0046] (3) Modification process: First, add 1000g of activated phlogopite to a high-speed mixer (with heating function) and preheat to 90°C under low-speed stirring (500rpm); then, spray the prepared KH-550 hydrolysate into the phlogopite powder slowly and evenly through an atomizing nozzle under high-speed stirring (1500rpm) for 15-20 minutes; after spraying, raise the temperature of the mixer to 110°C and continue the reaction for 45-60 minutes while maintaining high-speed stirring; finally, take out the processed material and place it in a vacuum oven and vacuum ripen at 120°C for 2 hours to obtain modified phlogopite with hydrophobic surface and good affinity with nylon matrix.

[0047] The formulations of Examples 1-5 and Comparative Examples 1-7 are shown in Table 1. In Table 1, the antioxidant consists of 0.2 parts of antioxidant 1098 and 0.2 parts of copper salt antioxidant H324, and the other additives consist of 0.2 parts of lubricant BRO-R05 and 0.4 parts of black masterbatch.

[0048] The preparation method of the example is as follows: Weighed polyamide resin, antioxidant, and other additives are mixed evenly in a high-speed mixer to obtain mixture A, which is added from the main feed of a twin-screw extruder; modified phlogopite and negative thermal expansion additive are mixed evenly in a high-speed mixer to obtain mixture B; flat glass fibers and mixture B are added from two sides respectively; after melt extrusion, granulation, and drying, a polyamide composition with good appearance and low warpage is obtained. The preparation method of the comparative example is the same as the example, with the raw materials replaced or reduced according to the corresponding formulation.

[0049] The relevant performance tests were conducted according to the following test methods. After drying the materials obtained from each embodiment and comparative example at 100℃ for 8 hours, they were injection molded into standard specimens and simulated cover plates (300mm×200mm×2mm). The test items are as follows:

[0050] (1) Initial warpage: Measured after injection molding at 23℃ / 50%RH for 24 hours.

[0051] (2) Warpage after thermal shock test: 30℃×1h → 120℃×1h, 4 cycles, then cooled to 23℃ for measurement.

[0052] (3) Tensile strength test: measured according to ISO 527 standard.

[0053] Table 1. Component ratios (parts by weight) for Examples 1-5 and Comparative Examples 1-7

[0054]

[0055] Table 2 Performance test results of Examples 1-5 and Comparative Examples 1-7

[0056]

[0057] The performance test results are shown in Table 2. It can be seen that the examples using a PA6 and copolynylon composite matrix, combined with a quaternary synergistic design of flat glass fibers, modified phlogopite, and a negative thermal expansion agent, all exhibited low initial warpage and warpage after thermal shock treatment, demonstrating both good mechanical properties and dimensional stability. Using only the PA6 matrix without copolynylon (Comparative Example 1), replacing flat glass fibers with round glass fibers (Comparative Example 2), omitting the negative thermal expansion agent (Comparative Example 3), replacing modified phlogopite with unmodified phlogopite (Comparative Example 4) or talc (Comparative Example 5), and reducing the amount of modified phlogopite while increasing the amount of flat glass fibers (Comparative Example 6) all resulted in varying degrees of increased warpage. Even when reducing the amount of modified phlogopite while increasing the amount of the negative thermal expansion agent (Comparative Example 7), the warpage control effect was still inferior to the examples. These results indicate that the synergistic effect of the components in a specific ratio is key to achieving low warpage performance.

[0058] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. Any changes made by those skilled in the art after reading the specification of the present invention, as long as they are within the scope of the claims of the present invention, will be protected by patent law.

Claims

1. A low-warpage polyamide material for large-size thin-walled covers, characterized in that, It is composed of the following components in parts by weight: 60-70 parts polyamide resin, 5-10 parts flat glass fiber, 15-25 parts modified phlogopite, 1-5 parts negative thermal expansion agent, 0.2-0.5 parts antioxidant, and 0.2-1 parts other additives.

2. The low-warpage polyamide material for large-size thin-walled covers according to claim 1, characterized in that, The polyamide resin is a mixture of low-viscosity PA6 resin and copolymer nylon resin, with a weight ratio of PA6 resin to copolymer nylon of 1:3 to 2:

1.

3. The low-warpage polyamide material for large-size thin-walled covers according to claim 2, characterized in that, The low-viscosity PA6 has a relative viscosity of 2.0, a melt flow rate of 31 g / 10 min, and a melting point of 220 °C.

4. The low-warpage polyamide material for large-size thin-walled covers according to claim 2, characterized in that, The copolymer nylon is a copolymer of PA6 and PA66, with a relative viscosity of 2.5, a melt flow rate of 4.6 g / 10 min, and a melting point of 202℃.

5. The low-warpage polyamide material for large-size thin-walled covers according to claim 1, characterized in that, The flat glass fiber has a flat cross-section with an aspect ratio of 2:1 to 6:

1.

6. The low-warpage polyamide material for large-size thin-walled covers according to claim 1, characterized in that, The negative thermal expansion additive is a zirconium phosphate-based negative thermal expansion material, which is cubic in appearance and has a density of 0.2 g / cm³. 3 It exhibits a reversible negative coefficient of thermal expansion within the temperature range of 30–600℃, with a coefficient of thermal expansion of -3.5 × 10⁻⁶. -6 / K.

7. The low-warpage polyamide material for large-size thin-walled covers according to claim 1, characterized in that, The modified phlogopite is phlogopite powder that has been surface-treated with a silane coupling agent.

8. The low-warpage polyamide material for large-size thin-walled covers according to claim 7, characterized in that, The modified phlogopite is prepared through the following steps: (1) Acid washing and activation of phlogopite: Phenolic powder is soaked in dilute hydrochloric acid solution and stirred; then the acid-treated slurry is repeatedly filtered and washed with deionized water until the pH of the filtrate is 6.5-7.0; finally, the filter cake is dried to obtain activated phlogopite powder. (2) Preparation of KH-550 hydrolysate: Mix deionized water and anhydrous ethanol evenly, slowly add KH-550 silane coupling agent while stirring, adjust the pH to 8.0-8.5 with glacial acetic acid, pre-hydrolyze at 25°C to obtain a clear and transparent slightly alkaline hydrolysate. (3) Modification process: First, the activated phlogopite is preheated under low-speed stirring; then, the prepared KH-550 hydrolysate is slowly and evenly sprayed into the phlogopite powder through an atomizing nozzle under high-speed stirring. After spraying, the temperature is increased and the reaction continues with high-speed stirring. Finally, the treated material is taken out and vacuum-cured to obtain modified phlogopite with a hydrophobic surface and good affinity with the nylon matrix.

9. The low-warpage polyamide material for large-size thin-walled covers according to claim 8, characterized in that, The modified phlogopite is prepared through the following steps: (1) Acid washing and activation of phlogopite: Phenolic mica powder was soaked in a 0.1 mol / L dilute hydrochloric acid solution with a solid-liquid ratio of 1:5 and stirred at 40°C for 30 minutes; then the acid-treated slurry was repeatedly filtered and washed with deionized water until the pH of the filtrate was 6.5-7.0; finally, the filter cake was dried at 120°C for 4 hours to obtain activated phlogopite powder. (2) Preparation of KH-550 hydrolysate: In an independent container, prepare the hydrolysate according to the following ratio: mix 1000g of deionized water and 3000g of anhydrous ethanol evenly, and slowly add 15g of KH-550 silane coupling agent while stirring. Adjust the pH to 8.0-8.5 with glacial acetic acid and pre-hydrolyze at 25°C for 30 minutes to obtain a clear and transparent slightly alkaline hydrolysate. (3) Modification process: First, add 1000g of activated phlogopite to a high-speed mixer and preheat it to 90℃ under low-speed stirring at 500rpm. Then, the prepared KH-550 hydrolysate is slowly and evenly sprayed into the phlogopite powder through an atomizing nozzle under high-speed stirring at 1500rpm for 15-20 minutes. After spraying, the temperature of the mixer is raised to 110℃ and the reaction is continued for 45-60 minutes while maintaining high-speed stirring. Finally, the treated material is taken out and placed in a vacuum oven and vacuum-cured at 120℃ for 2 hours to obtain modified phlogopite with hydrophobic surface and good affinity with nylon matrix.

10. A method for preparing the low-warpage polyamide material for large-size thin-walled covers according to any one of claims 1 to 9, characterized in that, The steps are as follows: The weighed polyamide resin, antioxidant and other additives are mixed evenly in a high-speed mixer to obtain mixture A, which is added from the main feed of the twin-screw extruder; the modified phlogopite and negative thermal expansion additive are mixed evenly in a high-speed mixer to obtain mixture B; flat glass fibers and mixture B are added from the two sides respectively; after melt extrusion, granulation and drying, a polyamide composition with good appearance and low warpage is obtained.

Citation Information

Patent Citations

  • Polyamide composite material and preparation method thereof

    CN101875780A

  • High temperature resistant low warping nylon composite material of automobile engine hood shield and preparation method thereof

    CN108102363A